Can Income Smothing Be Influenced By Ownership And Religiosity: An Empirical Study On JII Group Companies Listed On The IDX - Raden Arief Wibowo; Novelia Melati Sukma (Accounting and Finance Studies, 2022)
This research was conducted to examine the effect of Internal Ownership, Institutional Ownership and Religiosity on Income Smoothing, a study of JII Group Companies on the Indonesia Stock Exchange 2016-2018 period. The population used in this study as the object of the company were all 30 companies of the JII group listed on the 2016-2018 Indonesian Stock Exchange, while 17 companies were used as the object of research (samples). The sampling technique used was purposive sampling method. Hypothesis testing uses multiple linear regression analysis. The results of this study indicate that internal ownership has no significant effect on income smoothing, while institutional ownership has a significant effect on income smoothing and religiosity has no significant effect on income smoothing